The book stops here eaudiobook - Carlisle, Kate (Bibliophile Mystery, 2014)
Brooklyn Wainwright is thrilled to be appearing on the hit TV show This Old Attic as a rare-book expert. Her first subject is a very valuable first-edition copy The Secret Garden. Its owner, Vera, is eager to have Brooklyn recondition it for resale. But a furious man viciously accosts Brooklyn, claiming that Vera found the first edition at his garage sale, and he wants it back - or else. Randolph Rayburn, the handsome host of This Old Attic, is terrified by the man's threats. He confides in Brooklyn that he fears he is being stalked. In the days that follow, Brooklyn visits Vera's flower shop...and discovers her dead. Brooklyn had better find the clever killer soon or more than her chance at prime time may be canceled...permanently.